Enhanced immune response outperform aggressive cancer biology and is associated with better survival in triple-negative breast cancer - Masanori Oshi; Ankit Patel; Rongrong Wu; Lan Le; Yoshihisa Tokumaru; Akimitsu Yamada; Li Yan; Ryusei Matsuyama; Takashi Ishikawa; Itaru Endo; Kazuaki Takabe (npj Breast Cancer, 2022)
Abstract Although the value of tumor-infiltrating lymphocytes is well known, the clinical relevance of an increased immune response, specifically in breast cancer, has not been investigated across large cohorts of patients using computational algorithms. Our hypothesis stated that an enhanced immune response is associated with an improvement in outcomes. To quantify the immune response, we utilized the allograft rejection score correlated with cytolytic activity and with all the other Hallmark immune-related gene sets. The score reflected the amount of infiltrating immune cells that correlated with the immune checkpoint molecule expressions, including CD4+ and CD8+ T cells, T helper type 1 (Th1) and type 2 (Th2) cells, M1 macrophages, B cells, and plasmacytoid dendritic cells (pDC). A high score was associated with high levels of intratumor heterogeneity, homologous recombination defects, mutation rate, histological grade, advanced stage, and lymph node metastasis. Breast malignancy with a high score enriched immune-related gene sets and pro-cancer-related gene sets, including epithelial–mesenchymal transition and KRAS pathway, in ER-positive/HER2-negative and triple-negative breast cancer (TNBC) groups. TNBC had the highest score compared to other subtypes, and was associated with better survival. In conclusion, we found that breast cancer with a high immune response is associated with aggressive cancer biology, but with better survival in TNBC.